2012
DOI: 10.1111/j.1558-5646.2012.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biogeography of Sulawesi Revisited: Is There Evidence for a Vicariant Origin of Taxa on Wallace's “Anomalous Island”?

Abstract: Sulawesi, the largest island in the Indonesian biodiversity hotspot region Wallacea, hosts a diverse endemic fauna whose origin has been debated for more than 150 years. We use a comparative approach based on dated phylogenies and geological constraints to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 125 publications
10
166
0
1
Order By: Relevance
“…As noted by Stelbrink et al (2012) for Sulawesi, during periods of low sea-level islands would have made a larger 'target' for dispersing taxa, making it more likely that sea-route colonisations would occur. Java emerged as an island in the late Pliocene and the earliest (Satir) fauna arrived sometime in the early Pleistocene, probably during periods of low sea level (van den Bergh et al, 2001).…”
Section: Moorwood and Jungers (2009) And Van Den Bergh Et Al (2008)mentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Stelbrink et al (2012) for Sulawesi, during periods of low sea-level islands would have made a larger 'target' for dispersing taxa, making it more likely that sea-route colonisations would occur. Java emerged as an island in the late Pliocene and the earliest (Satir) fauna arrived sometime in the early Pleistocene, probably during periods of low sea level (van den Bergh et al, 2001).…”
Section: Moorwood and Jungers (2009) And Van Den Bergh Et Al (2008)mentioning
confidence: 99%
“…Sulawesi is east of Wallace's line, but appears to have been colonised multiple times by a wide range of taxa (Stelbrink et al, 2012). In terms of primates, seven species of Macaca are present (Abegg and Thierry, 2002), whose ancestor probably arrived from Borneo (Ziegler et al, 2007), in addition to a number of cryptic tarsier species (Shekelle et al, 2010).…”
Section: <Insert Figure 2 Near Here>mentioning
confidence: 99%
“…More recently, it has been suggested that colonisations of Sulawesi started during the early Miocene, and that speciation events happened as early as 20 Mya (Stelbrink et al 2012). Patou et al (2008) proposed that the Hemigalinae diverged 15.4-8.4 Mya, which corresponds to the dates of origin of several Sulawesi taxa (Stelbrink et al 2012). These findings suggest that the Sulawesi palm civet diverged from the other species more than 10 Mya, which is supported by its high Cytb divergence (12.0-14.9%) from its relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Hall (2001) found evidence of a land bridge west of Sulawesi ca 20 million years ago (Mya), and suggested faunal exchanges between Sulawesi and the rest of Southeast Asia occurred ca 10 Mya. More recently, it has been suggested that colonisations of Sulawesi started during the early Miocene, and that speciation events happened as early as 20 Mya (Stelbrink et al 2012). Patou et al (2008) proposed that the Hemigalinae diverged 15.4-8.4 Mya, which corresponds to the dates of origin of several Sulawesi taxa (Stelbrink et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The answer is 'You wouldn't. ' Similarly, the fact that primates have not been able to colonise Australasia from Sulawesi should not come as a huge surprise given that (1) Sulawesi has not always been so close to Australasian land (Stelbrink et al 2012), and (2) the primates (macaques and tarsiers) of the island might have arrived there only within the past 3 million years (Ziegler et al 2007;Driller et al 2015, their fig. 1e).…”
Section: Ratites and Primatesmentioning
confidence: 99%